2006
DOI: 10.1007/s00181-005-0047-0
|View full text |Cite
|
Sign up to set email alerts
|

Modeling probabilities of patent oppositions in a Bayesian semiparametric regression framework

Abstract: Markov Chain Monte Carlo, Bayesian semiparametric binary regression, Bayesian P-splines, Patent opposition,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…This result is in contradiction with earlier empirical evidence (Graham et al, 2002;Jerak and Wagner, 2003;Reitzig, 2004a), though the ACCSRC variable had only been tested as a determinant of oppositions. However, the same authors as well as Harhoff and Hall (2002) found positive and significant coefficients for accelerated examination requests.…”
Section: Granted Patents Filed 1990-1995 -Robust Standard Errors -Coecontrasting
confidence: 99%
“…This result is in contradiction with earlier empirical evidence (Graham et al, 2002;Jerak and Wagner, 2003;Reitzig, 2004a), though the ACCSRC variable had only been tested as a determinant of oppositions. However, the same authors as well as Harhoff and Hall (2002) found positive and significant coefficients for accelerated examination requests.…”
Section: Granted Patents Filed 1990-1995 -Robust Standard Errors -Coecontrasting
confidence: 99%
“…In particular, these real options are subject to uncertainty, i.e. the value of the options changes as time evolves and new information about the investment project comes in (Wu, Yen 2007;Wörner, Grupp 2003;Jerak, Wagner 2006;Ernst et al 2010;Verdu et al 2012). Three levels of real option thinking can be distinguished (Faulkner 1996;Wu, Yen 2007;Wörner, Grupp 2003;Dissel et al 2005).…”
Section: Review and Classification Of Technology Valuation Methodsmentioning
confidence: 99%
“…Among them, for instance: (Wong and Kohn, 1996;Li, 2000;Smith et al, 2000;Kandala et al, 2001;Panagiotelis and Smith, 2008;Ryu et al, 2011) were those who use regression spline with Bayesian approach, while (Lang and Brezger, 2004;Jerak and Wagner, 2006;Nott, 2006;Costa, 2008;Marley and Wand, 2010;Shen, 2011) were those who use p-spline with Bayesian approach. Wang (2011) used a smoothing spline in semiparametric regression model whose parametric components are linear patterned with Bayesian approach.…”
Section: That Comparesmentioning
confidence: 99%